Early Help in Early Years: Developing a Universal Assessment Tool. Issue 3 (3rd July 2019) - Redwood, Tracey; Neill, Sarah; Church, Sarah; Spencer, Melinda
ABSTRACT: Effective assessment tools are an essential element of early identification of problems, enabling early intervention in the first two or so years of life. This article reports on the development and evaluation of a Universal Assessment Tool for Early Help in Early Years. The project aim was to develop, pilot and evaluate a new universal assessment tool named "My Family Profile" for use within Northamptonshire, United Kingdom, from pregnancy until a child reaches 2/2.5 years of age. A flowchart demonstrates the stages of the process including how each step contributed toward the tool and end report (Neill et al., 2015). The project used an intervention design enabling collaborative inter-agency working and ensured parents were engaged throughout the process. The methods used in developing the tool incorporated collaborative working, content analysis, format requirements, questioning styles and information sharing. The tool was evaluated using focus groups and individual interviews with parents, an online evaluation questionnaire and audit of completed assessment forms with practitioners. The resulting report (Neill et al., 2015) contained "My Family Profile" highlighted five key recommendations: (1) It is developed in a digital format with secure "cloud" storage, accessible from all IT platforms in use by child health/care professionals; (2) it is implemented with a comprehensive training program for professionals; (3) it is formally evaluated following implementation; (4) it is extended up to school entry and through school years; and (5) it is developed for use within other locations in the United Kingdom.